Dihydromyricetin functions as a tumor suppressor in hepatoblastoma by regulating SOD1/ROS pathway - Guo, Tong; Wang, Xitong; Zhang, Gensheng; Xia, Tian; Zhu, Runzhi; Tou, Jinfa (Frontiers in Oncology, 2023)
Background Hepatoblastoma has an unsatisfactory prognosis, and traditional chemotherapy has strong side effects. Dihydromyricetin is a flavonoid extracted from a woody vine of the genus Serpentine in the family Vitaceae, with effects such as preventing alcoholic liver and reducing the incidence of liver cancer. However, the effect of DHM on hepatoblastoma and its specific pathway are still unclear. Purpose The purpose of this study was to investigate the effects of DHM on children's hepatoblastoma and its related mechanisms. Methods CCK-8 assays were used to measure proliferation. Apoptosis and reactive oxygen species (ROS) were analyzed by flow cytometry. Apoptotic cells were observed using Hoechst 33342 staining and fluorescence microscopy. Protein expression levels in HuH-6 and HepG2 cells were determined by western blotting. Results We found that DHM was able to inhibit the growth and increase cellular mortality in HuH-6 and HepG2 cells. Furthermore, DHM decreased the intracellular ROS level and increased the expression of SOD1. ROS scavenger NAC promoted apoptosis, while the use of SOD1 inhibitor LCS-1 weakened the ROS scavenging effect of DHM , and to some extent reduced the killing effect of DHM on hepatoblastoma cells. Conclusion These results suggest that regulating SOD1/ROS pathway to induce apoptosis is one of the potential mechanisms of DHM as a tumor suppressor in hepatoblastoma. Therefore, DHM may be a novel candidate for inhibiting hepatoblastoma growth and deserves further study.